PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BOGA ALAM MAKMUR - Febriyani, Alfina; Amas Priatna, Isep (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of work discipline and work stress on employee work productivity at PT. Boga Alam Makmur both partially and simultaneously. The method used is quantitative descriptive. The sampling technique used saturated sampling and the sample obtained in this study amounted to 53 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study are a discussion of the effect of work discipline (X1) and work stress (X2) on employee work productivity (Y), as follows: work discipline (X1) has a significant effect on employee work productivity (Y) with the regression equation Y = 7.700 + 0.805X1, the correlation coefficient value is 0.862 where the value is in the interval 0.800 - 1.000, meaning that the two variables have a very strong relationship. Determination value 74.3%. Hypothesis test obtained tcount value > ttable or (12.158 > 2.009). Thus H0 is rejected and H1 is accepted, this shows that there is a significant influence between work discipline (X1) on employee work productivity (Y). Work stress (X2) has a significant effect on employee work productivity (Y) with the regression equation Y = 62.022 - 0.903X2, the correlation coefficient value is -0.751 where the value is in the interval 0.600 - 0.799, meaning that both variables have a strong relationship level. The determination value is 56.4%. Hypothesis testing obtained a value of -tcount > -ttable or (-8.126 > -2.009). Thus H0 is rejected and H2 is accepted, this shows that there is a significant influence between work stress (X2) on employee work productivity (Y). Work discipline (X1) and work stress (X2) have a significant effect on employee work productivity (Y) with the regression equation Y = 21.790 + 0.632X1 - 0.302X2. The correlation coefficient value is 0.879 where the value is in the interval of 0.800 - 1.000, meaning that the two variables have a very strong level of relationship. The determination value is 77.2%. The hypothesis test obtained the value of fcount > ftable or (84.673 > 3.183). Thus, H0 is rejected and H3 is accepted, this shows that there is a significant simultaneous influence between work discipline (X1) and work stress (X2) on employee work productivity at PT. Boga Alam Makmur.